A follow-up study on the characterization and health risk assessment of heavy metals in ambient air particles emitted from a municipal waste incinerator in Zhejiang, China. (May 2020) - Xu, Peiwei; Chen, Yuan; He, Shengliang; Chen, Weizhong; Wu, Lizhi; Xu, Dandan; Chen, Zhijian; Wang, Xiaofeng; Lou, Xiaoming
Abstract: To confirm our hypothesis that inhalation might be the primary exposure route of heavy metals for children living in proximity to a municipal waste incinerator (MWI), we conducted a one-year follow up study to characterize the distributions of heavy metals featured in different types of ambient air particles, including PM1, PM2.5 and PM10, at two exposure sites near the MWI (E1 and E2) and one control site (C) in Zhejiang, China. Particle samples were collected by a mid-volume sampler and heavy metals were determined by the inductively coupled plasma mass spectrometry method. The mass concentrations of PM1, PM2.5 and PM10 were 52.0, 85.8 and 100.3 μg/m 3 at E1 site, while the concentrations were 40.2, 92.1 and 106.6 μg/m 3 at E2 site and 33.4, 55.6 and 66.1 μg/m 3 at C site, respectively. Both E1 and E2 had higher PM1, PM2.5 and PM10 levels than C site. The levels of pollution were season dependent, with autumn having the highest levels of PM1, PM2.5 and PM10 across all three sampling sites. Regarding the distributions of heavy metals, Pb accounted for the majority of the seven metals in all groups, ranging from 43.2% to 51.3%, followed by Mn that ranged from 22.0% to 32.0%. The Pb levels of PM1, PM2.5 and PM10 in the MWI area were 22.6, 34.2 and 36.2 ng/m 3, respectively, while Mn levels were 10.1, 20.0 and 23.5 ng/m 3, respectively. The health risk assessment results suggested that residents were suffering high non-carcinogenic risk posed by MWI-emitted particle-bound toxic metals, as well as the high lifetime carcinogenic risk. This study revealed that ambient air, no matter whether near or far away from an MWI, bore more PM1, PM2.5 and PM10 particles than general, non-polluted ambient air, especially in autumn. Highlights: . Ambient air around the MWIs bore more particles than ambient air in general area. . PM1, PM2.5, and PM10 particles exhibited highest mass concentrations in autumn. . Pb and Mn accounted for the majority of heavy levels in ambient particles. . Residents living near the MWIs were suffering high non-carcinogenic risk. . Adults living near the MWIs were suffering high carcinogenic risk.